Victimology Review of Sago Factory Waste Disposal in Soren Village and Sungai Baru Village, Gaung, Indragiri Hilir - muhammad iqbal,; Riky Novarizal, (Sisi Lain Realita, 2024)
Industrial waste disposal is one of the environmental problems frequently encountered by communities in various regions, including Soren Village and Sungai Baru Village. The sago factories operating around these two villages produce large amounts of waste, which is often poorly managed, leading to environmental contamination. This study aims to illustrate the environmental pollution caused by the activities of the sago factories in Soren Village over the past eight years since this thesis was written. The research employs a qualitative descriptive approach. Based on the findings, it is concluded that the environmental pollution resulting from the activities of the sago factories in Soren Village, Indragiri Hilir Regency, primarily manifests as water pollution. The water pollution is evident from the nearest river's water, which has changed color and developed an odor, making it unusable for bathing, washing, and sanitation activities. This environmental pollution occurs because the factory activities do not comply with waste management standards, and the factory disposes of its waste into the river, resulting in victims from this waste disposal practice.